If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -6x = 3x + -3 Reorder the terms: 12 + -6x = -3 + 3x Solving 12 + -6x = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + -6x + -3x = -3 + 3x + -3x Combine like terms: -6x + -3x = -9x 12 + -9x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + -9x = -3 + 0 12 + -9x = -3 Add '-12' to each side of the equation. 12 + -12 + -9x = -3 + -12 Combine like terms: 12 + -12 = 0 0 + -9x = -3 + -12 -9x = -3 + -12 Combine like terms: -3 + -12 = -15 -9x = -15 Divide each side by '-9'. x = 1.666666667 Simplifying x = 1.666666667
| 6m+3(2m+5)+7=0 | | 6=n-8 | | -2AH=V^2-U^2 | | 28+3p=-4p | | x-2y^2-8y=3 | | 19x-4=10x-40 | | x-3/3=41/2 | | 4x-5x+x-7+2x= | | 4-3Y=30 | | 7x+8-x=35 | | 20=-12+u | | -1=r/4-2 | | -3z-7z+4=0 | | 2n^4+16n^2+21=x | | 63w-44-47w=-140 | | x-8y-2y=3 | | 0.20x=46 | | (2x+3)/5=9 | | 1-9x=0 | | (5y+5)-(2+4y)=9 | | 6x+7(2x-17)=41 | | 3(4x+6)=-35+41 | | 3x-2/5=x-2 | | b/9+1/4=11 | | 2x-6x-65=63 | | 3(2x+9)=5(x-2) | | 2AH=V^2-U^2 | | 6x-50=10x+73 | | -0.7x+0.8x+8=-2 | | 2ln(x)=ln(x+6) | | 3x=(4x-15) | | 2y+8y-3=x |